1991
DOI: 10.1149/1.2085393
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion Behavior of a P130x Graphite Fiber Reinforced 6063 Aluminum Composite Laminate in Aqueous Environments

Abstract: The aqueous corrosion behavior of 0/90 cross-plied P130x graphite fiber reinforced 6063 A1 composite laminates was studied in deaerated and aerated aqueous Na2SO4 and NaC1 solutions using immersion and electrochemical techniques. Special emphasis was given to the identification of the principal mechanism(s) of corrosion. It was demonstrated conclusively via microscopic and electrochemical considerations that galvanic attack of the matrix was by far the dominant mechanism of corrosion in both solutions when A1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Dutta et al [16] suggested that, compared with the matrix, obvious stress corrosion occurred in the metal matrix composites (MMCs) as a result of large thermal stress in the matrix surrounding the fibers during fabrication. However, it was not the main factor in corrosion.…”
Section: Resultsmentioning
confidence: 99%
“…Dutta et al [16] suggested that, compared with the matrix, obvious stress corrosion occurred in the metal matrix composites (MMCs) as a result of large thermal stress in the matrix surrounding the fibers during fabrication. However, it was not the main factor in corrosion.…”
Section: Resultsmentioning
confidence: 99%
“…The galvanic effect between the fiber and matrix has also been observed for 0/90 cross plied Al 6063/P130 C MMC laminate in aerated and deaerated Na 2 SO 4 and NaCl solutions. 17 The galvanic corrosion rate of the MMCs increased when the solution is in an aerated condition or at a low pH. The presence of the sulfite * Electrochemical Society Student Member.…”
mentioning
confidence: 99%
“…The presence of the sulfite ion in the sulfate solution at low pH enhanced the galvanic action and the nucleation rate of the pits, but decreased the growth rate of the pits. 17 Hihara and Latansion, 18 observed that the presence of residual chlorides in the microstructure of Al/C MMCs that were fabricated by the titanium-boron vapor deposition technique dramatically changed the corrosion behavior. The localized corrosion began at microstructural chloride regions and led to the exfoliation of Al/C plates.…”
mentioning
confidence: 99%